2002
DOI: 10.1002/cncr.11009
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter Phase II study of the intravenous administration of liposomal tretinoin in patients with acquired immunodeficiency syndrome‐associated Kaposi's sarcoma

Abstract: Fluoreszenzlicht wird genutzt, um einen chemoselektiven Zugang zu den cis/trans‐Isomeren N‐unsubstituierter Imine zu erhalten. Die Synthese wird als Ein‐Topf‐Sequenz aus Imin‐Bildung und asymmetrischer Allylierung von Benzylazid mit 1 als Katalysator geführt. Ipc=Isopinocampheyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Experimental studies report growth-inhibitory effects on osteosarcoma [47], rhabdomyosarcoma [40], and AIDS-associated Kaposi sarcoma [15]. Approximately 30% of patients with AIDSassociated Kaposi sarcoma have a substantial clinical response to ATRA treatment [8], and one case report suggested ATRA treatment combined with interferon-a was effective against inoperable metastatic osteosarcoma [48]. Our data demonstrate SS cell lines were far more sensitive to treatment with ATRA than the other types of tumors analyzed, and NMS-2, a cell line derived from MPNST, which in clinical practice is resistant to all chemotherapeutic treatments, also showed marked sensitivity to treatment with ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies report growth-inhibitory effects on osteosarcoma [47], rhabdomyosarcoma [40], and AIDS-associated Kaposi sarcoma [15]. Approximately 30% of patients with AIDSassociated Kaposi sarcoma have a substantial clinical response to ATRA treatment [8], and one case report suggested ATRA treatment combined with interferon-a was effective against inoperable metastatic osteosarcoma [48]. Our data demonstrate SS cell lines were far more sensitive to treatment with ATRA than the other types of tumors analyzed, and NMS-2, a cell line derived from MPNST, which in clinical practice is resistant to all chemotherapeutic treatments, also showed marked sensitivity to treatment with ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter trial was conducted to determine the efficacy and toxicity of escalating dosages of IV liposomal tretinoin (alltrans-retinoic acid) administered once or three times weekly in patients with AIDS-related KS. 343 A 3 times per week dosing schedule was noted to be more effective compared with a once-a-week schedule without any significant difference in toxicity.…”
Section: Retinoidsmentioning
confidence: 96%
“…This study suggested that coadministration of PXR ligands can increase ATRA metabolism through activation of the PXR-CYP3A pathway, which might be a mechanism for some form of ATRA resistance. Other PXR target transporters might also be involved.All-trans retinoic acid (ATRA) is currently used as a chemotherapeutic agent against acute promyelocytic leukemia (APL), breast cancer, Kaposi's sarcoma, and glioma (Muindi et al, 1992b;Defer et al, 1997;Toma et al, 2000;Bernstein et al, 2002). ATRA modulates the transcription of a set of genes associated with cellular apoptosis, growth, and differentiation by binding to retinoic acid receptors (RARs) and retinoid X receptors (RXRs).…”
mentioning
confidence: 99%